Essays on typology of Iranian Languages - Korangy, Alireza; Mahmoodi-Bakhtiari, Behrooz (Trends in linguistics. Studies and monographs ;, 2019)
The Iranian languages are one of the world's major language families. With an estimated 150 to 200 million native speakers, these languages constitute the western group of the larger Indo-Iranian family, which represents a major eastern branch of the Indo-European languages. Geographically, the Iranian Languages are spoken from Central Turkey, Syria and Iraq in the West to Pakistan and western edged of Xinjiang Uygur Autonomous Region of China in the east. Iranian languages have long been among the major interests of the philologists and general linguists, and European scholars have made tremendous contributions to the study of this language family. In light of such efforts, now we know that the Iranian languages can be historically divided into three phases, that are old, middle and new Iranian languages, and the new Iranian languages may be generally grouped as Eastern and Western. In recent years, the orientation towards typology has led to the appearance of somewhat more ponderance on the subject but the work has not included description of some of the very important languages of the Caspian, and or of the religious minorities (such as those of the Zoroastrians or the Jewish community), of the four-fold Central Plateau dial.